Firefight! : the history of personal firepower - Newark, Peter (Newton Abbot, Devon : David & Charles Publishers ; New York, NY : Distributed in the United States by Sterling Pub. Co., 1989)
From cowboys in a Western-style shoot-out to Moslem terrorists in action in the 1980s, guns and gunfighters have determined the course of history the world over. With this book you can relive the great story of firefighting and look forward to the Scicon soldier of the twenty-first century.
Includes bibliographical references (page 185) and index.
Keywords: Firearms -- History; Infantry drill and tactics -- History; Firearms; History